Implication of fibroblast growth factors in epileptogenesis-associated circuit rearrangements - Paradiso, Beatrice; Zucchini, Silvia; Simonato, Michele (Frontiers in Cellular Neuroscience, 2013)
The transformation of a normal brain in epileptic (epileptogenesis) is associated with extensive morpho-functional alterations, including cell death, axonal and dendritic plasticity, neurogenesis, and others. Neurotrophic factors (NTFs) appear to be very strongly implicated in these phenomena. In this review, we focus on the involvement of fibroblast growth factor (FGF) family members. Available data demonstrate that the FGFs are highly involved in the generation of the morpho-functional alterations in brain circuitries associated with epileptogenesis. For example, data on FGF2, the most studied member, suggest that it may be implicated both in seizure susceptibility and in seizure-induced plasticity, exerting different, and apparently contrasting effects: favoring acute seizures but reducing seizure-induced cell death. Even if many FGF members are still unexplored and very limited information is available on the FGF receptors, a complex and fascinating picture is emerging: multiple FGFs producing synergic or antagonistic effects one with another (and/or with other NTFs) on biological parameters that, in turn, facilitate or oppose transformation of the normal tissue in epileptic. In principle, identifying key elements in these phenomena may lead to effective therapies, but reaching this goal will require confronting a huge complexity. One first step could be to generate a “neurotrophicome” listing the FGFs (and all other NTFs) that are active during epileptogenesis. This should include identification of the extent to which each NTF is active (concentrations at the site of action); how it is active (local representation of receptor subtypes); when in the natural history of disease this occurs; how the NTF at hand will possibly interact with other NTFs. This is extraordinarily challenging, but holds the promise of a better understanding of epileptogenesis and, at large, of brain function.